To simplify the expression, let's start by distributing the coefficients.
1/2( z+4) = 1/2 * z + 1/2 * 4 = 1/2z + 2
3(1/4z+1) = 3 * 1/4z + 3 * 1 = 3/4z + 3
Now we can substitute these simplified terms back into the original expression:
1/2(z+4) - 3(1/4z+1) = 1/2z + 2 - (3/4z + 3)
Since the second term is being subtracted, we can distribute the negative sign:
= 1/2z + 2 - 3/4z - 3
Now let's combine like terms:
= (1/2z - 3/4z) + (2 - 3)
To combine the fractions, we need a common denominator. The least common multiple of 2 and 4 is 4. So we can rewrite the fractions with the common denominator:
= (2/4z - 3/4z) + (8/4 - 12/4)
= (-1/4z) + (-4/4)
Now we can simplify the fractions:
= -1/4z - 1
So the final simplified form is -1/4z - 1.
Subtract 1/2(z+4)-3(1/4z+1) use fractions in the final form
1 answer